1993
DOI: 10.1037/0033-2909.114.1.100
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dieting on eating behavior: A three-factor model.

Abstract: I review and critique restraint theory and develop a 3-factor model of dieting behavior. The factors--frequency of dieting and overeating, current dieting, and weight suppression--are embedded within a 3-dimensional grid that also considers mechanisms mediating the effects of dieting and the influence of weight status. I argue that the eating behavior exhibited by restrained eaters stems from their frequent dieting and overeating in the past rather than from their current state of dietary or cognitive restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
328
3
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(373 citation statements)
references
References 156 publications
23
328
3
3
Order By: Relevance
“…As noted by Lowe (1993), the dietary restraint construct could involve: 1) the frequency of dieting/overeating, 2) current dieting (or caloric restriction), and 3) weight suppression. Others have also suggested that some measures of dietary restraint may also measure susceptibility for overeating.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted by Lowe (1993), the dietary restraint construct could involve: 1) the frequency of dieting/overeating, 2) current dieting (or caloric restriction), and 3) weight suppression. Others have also suggested that some measures of dietary restraint may also measure susceptibility for overeating.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the measures, DEBQ, EI, and RS, contain questions that ask directly about an intention to engage in dieting to manage body weight, and in principle all four instruments ask questions about actual behavior that would result in caloric restriction, i.e., what Lowe (1993) called "current dieting." Thus, all four measures ask questions related to the frequency or intensity of dieting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herman and Polivy (1975) expanded Nisbett's idea by suggesting that normal weight individuals are also influenced by a cultural drive for thinness. This drive for thinness leads them, like overweight individuals, to restrain their eating to below their natural set point in order to lose weight, resulting in a vulnerability for externally triggered eating and overeating (Lowe, 1993). Many more individuals, therefore, regardless of their weight, are at risk for dysregulated eating.…”
Section: Models Of Eating and Self-regulationmentioning
confidence: 99%